Ekspresi Tartrate-Resistant Acid Phosphatase-5b pada Epifisis Tulang Femur Tikus Ovariektomi yang Mengkonsumsi Calcitriol dan Raloxifene (TARTRATE-RESISTANT ACID PHOSPHATASE-5b EXPRESSION OF EPIPHYSYS DISTALIS FEMUR OVARIECTOMIZED RATS CONSUMING CALCITRIO - ., Hartiningsih; Anggraeni, Devita (Jurnal Veteriner, 2016)
Tartrate resistant alkaline phosphatase 5b (TRACP5b) is secreted by osteoclasts during bonedifferentiation and resorption. The objective of the research was to study TRAP5b expression inovariectomized Wistar rat consuming the combinations of calcitriol and raloxifene supplementation foreight weeks. Twenty five female Wistar rats aged eight weeks were randomly divided into five groups:normal control (NK), ovariectomy control (OVK), ovariectomy+calcitriol supplementation (OVD),ovariectomy+ raloxifene supplementation (OVR), and ovariectomy+calcitriol+ raloxifene supplementation(OVDR). At the end of the treatment, blood samples were taken from plexus orbitalis medialis forestrogen analysis. All rats were euthanized, the uteri were taken and weighed. Left femur was taken forhistopatological examination and immunohistochemistry TRAP5b using monoclonal antibody anti TRAP5bwhich was detected with streptavidin-biotin. The results showed that estrogen levels of the rats in OVKgroup were significantly decreased compared to the rats in NK group, meanwhile estrogen levels in the OVDR rat group were significantly decreased compared to the NK and OVK rat group. Histopathologicalobservation of distal femur epiphysis in group NK showed normal structure, meanwhile, distal femurepiphysis in OVK group was found osteoporosis, with some abnormalities, such as: increased of bonemarrow space, domination of adipocytes in the bone marrow, and decrease of trabecular bone speculum inepiphysis. Histopathological findings of distal femur epiphysis in OVDR group were increased of trabecularbone speculum in epiphysis and the domination of adipocytes in the bone marrow of epiphysis.Immunohistochemistry of distal femur epiphysis in OVDR group revealed increasing tartrate resistantalkaline phosphatase 5b (TRAP5b) expression in trabecular bone, which was located in bone marrow spaceand trabecular speculum surface as well. It can be concluded that the combination of calcitriol and raloxifenesupplementation in ovariectomized rats aged 8 weeks increases TRACP5b expression as a marker for theincrease of osteoclast acitivity in bone resorption, which may lead to the formation of the bone.
Keywords: calcitriol; ovariectomy; raloxifene